Pediatric Manubriosternal Dislocation: A Case Report and Review of Literature - Yancovich, Shannon (Cureus, 2021)
Pediatric sternal dislocation is an extremely rare event, with less than 15 cases reported in the literature. We report the case of a traumatic sternal segment dislocation in an 8-year-old male that was caused by an unsuccessful backflip resulting in a direct force to the chest. The diagnosis was made by chest computed tomography. Open reduction and internal fixation (ORIF) were performed with a good outcome noted at follow-up. In addition to a thorough description of this case, we have included an organized review of existing literature with an aim to establish trends in presentation, clinical course, and outcomes among sternal dislocation in the pediatric population.